Active deformation in Ecuador enlightened by a new waveform-based catalog of earthquake focal mechanisms. (August 2019) - Vaca, Sandro; Vallée, Martin; Nocquet, Jean-Mathieu; Alvarado, Alexandra
Abstract: The recent development of a national seismic broadband network in Ecuador enables us to determine a comprehensive catalog of earthquake focal mechanisms at the country-scale. Using a waveform inversion technique accounting for the spatially variable seismic velocity structure across the country, we provide location, depth, focal mechanism and seismic moment for 282 earthquakes during the 2009–2015 period. Our results are consistent with source parameter determinations at the global scale for the largest events, and increase the number of waveform-based focal mechanism solutions by a factor of two. Our new catalog provides additional constraints on the active deformation processes in Ecuador. Along the Ecuador margin, we find a correlation between the focal mechanisms and the strength of interseismic locking at the subduction interface derived from GPS measurements: thrust earthquakes predominate in Northern Ecuador where interseismic locking is high, while the low-to-moderate locking in Central and Southern Ecuador results in variable fault plane orientations. Focal mechanisms for crustal earthquakes are consistent with the principal axis of strain rate field derived from GPS data and with the location of the main active faults. Our catalog helps to determine the earthquake type to be expected in each of the seismic zones that have recently been proposed for probabilistic seismic hazard assessment. Highlights: New waveform-based focal mechanism catalog of Ecuador seismicity. Links between focal mechanisms, subduction coupling and GNSS-derived strain rates. Better characterization of the earthquake types to be expected throughout Ecuador.